Adaptive fault-tolerant control for systems with exact band small gain conditions - Wang, Jianliang (2013)
This paper is concerned with the problem of adaptive fault-tolerant control for linear continuous-time systems with exact band small gain conditions against actuator partial faults. Based on the online estimation of actuator efficiency factors, an adaptive fault-tolerant controller is developed by exact band multi-objective optimal approach such that the resulting closed-loop system is asymptotically stable and satisfies exact band small gain condition for both normal and faulty cases. Finally, the effectiveness of the proposed method is illustrated via two numerical examples.